Causes of variations in the scale of tourism in Polish national parks - Miazek, Piotr (Turyzm/Tourism, 2020)
National parks are among the most frequently visited tourist places in Poland. Every year, millions of tourists travel to spend time there and their number is constantly rising. National parks take nearly 30% of all domestic tourism. However, the number of people visiting individual national parks strongly varies. Some parks are visited by millions, others by only several thousand. The article is an attempt to indicate the main causes of the varying number of tourists visiting national parks. By analysing individual features of tourism in specific national parks, especially in those where the differences are most visible, the author attempts to distinguish aspects which may explain this phenomenon.